PENGARUH SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS TERHADAP PENGENDALIAN PENDAPATAN PADA PERUM DAMRI BANDUNG - Yusup, Maulana; Sudrajat, Jajat (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2014)
Perum DAMRI Bandung is one of the state-owned company engaged in the field of services. Income on Perum DAMRI Bandung is cash receipts derived from the sale of the company’s activities in serving the public services in the field of public transport, especially in the provision of City Bus Transport Unit (UABK) Bandung, AKDP (Transportation City and Province), and bus transportation Government Assistance serves other similar buses. The intent of this study is to obtain an overall picture of the magnitude of the effect of the accounting information system of internal control of cash receipts for income. Authors in conducting this research using descriptive analysis method with field research data collection procedures (field research) that aims to obtain a clear picture of the research. Where the data collection was conducted through interviews, observation or field. Through research on the author, the obtained results, among others: the results of calculations between independent variables, namely cash receipts accounting information system and the dependent variable is the internal control of income has a strong relationship, as can be seen from the calculation of the correlation coefficient has a value of r = 0.911 and cash receipts accounting information systems applied Perum DAMRI Bandung contributed 87% to the revenue of internal control. Keywords: cash receipts; accounting information systems; revenue control.